Unravelling the pathological roles of anastasis in cancer recurrence - Ho Man Tang; Ho Lam Tang (Open Biology)
Can anastasis contribute to cancer recurrence? Anastasis is a cell recovery mechanism to spare dying cells after the initiation of the cell death process. Emerging studies interrogate anastasis as an unexpected escape tactic for cancer cells to evade cell death-inducing anti-cancer therapy, leading to recurrence. After anastasis, cancer cells display increased invasiveness and genomic instability, which could be associated with the common and fatal features of metastasis and drug resistance at the cancer recurrence. These studies open an encouraging new conceptual avenue for arresting cancer recurrence by targeting anastasis in cancer cells after conventional anti-cancer therapy. Here, we highlight recent findings towards unravelling pathological roles of anastasis in cancer recurrence, for the purpose of stimulating ideas and promoting the development of this new field of cancer research.